THE APPROPRIATE INTERVENTION TO IMPROVE PATIENT OUTCOME AMONG STROKE PATIENTS: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i2.139 - Eva Nilam Permata; Dewi Irawati (Alta Dharma Publisher, 2019)
Stroke has a deadly domino effect and is the number one cause of neurological defects in the world. Stroke patients can experience neurological deficits including cognitive impairment and disruption in fulfilling functional status reducing patient outcome. This literature review aims to identify the appropriate intervention to improve patient outcome among stroke patients. The authors conducted a literature search using several databases, namely ProQuest, EBSCO, Sage, and Science Direct from 2008 to 2018. The keywords appropriateness in the search were “stroke-patient”, “nursing intervention”, “patient outcome”. The literature search showed there are several nursing interventions for stroke patients that have an effect on increasing patient outcomes, namely intervention of dysphagia management, mobilization exercises, acupressure, cognitive enhancement, and self-management empowerment interventions. Nursing intervention given to stroke patients varies depending on the patient's response that arises as a result of a disorder related to the function of the part of the brain affected in stroke patients. Nurses through nursing interventions have a role in improving outcomes in stroke patients Keywords: Nursing Intervention; Patient Outcome; Stroke-Patient